Validation of visual analogue scales to assess occupational stress compared to the Karasek questionnaire: A cross sectional study - Maëlys Clinchamps; Bruno Pereira; Martial Mermillod; Morteza Charkhabi; Marek Zak; Jiao Jiao; Alistair Cole; Jean-Baptiste Bouillon-Minois; Frédéric Dutheil (PLoS ONE, 2026)
Background The Job Demand-Control-Support (JDCS) model is one of the most important tools for assessing work-related stress. However, its complexity highlights the need for simpler instruments, such as the Visual Analog Scale (VAS), for rapid assessment in occupational medicine. Objectives To validate three VAS corresponding to the main JDCS dimensions: job demand, job control, and social support. Method We conducted an observational cross-sectional validation study using a self-administered questionnaire completed twice, a week apart, at the participants’ convenience, to perform test-retest. Results We analysed 155 participants (60 for test and retest), mostly women around 40 years. Acceptability was excellent, with high response rates. Internal consistency analysis revealed moderate correlations between VAS and JDCS model main dimensions. Reliability assessed by Lin’s concordance correlation coefficient was acceptable for the VAS and higher for the JDCS. Mean VAS scores indicated significant differences between low and high demand, control, and social support, with cut-off values of 58, 71.5 and 63.5 respectively. For external validity, we mainly found high agreement between VAS and JDCS. Conclusions VAS are valid, quick, easy to use, and reliable tools for the assessment of job demand, job control and social support in daily clinical practice for primary prevention and diagnosis. Based on our findings, easier-to-remember cut-offs could be proposed at 60, 70, and 60 for VAS job demand, VAS job control, and VAS social support, respectively. However, when results are over the determined cut-off, we encourage the use of JDCS questionnaire. Trial registration ClinicalTrials.gov NCT05871411 .